PENGARUH IMMEDIET INSTRUMENTAL MUSIC HEARING THERAPY DENGAN PROGRESIVE MUSCLE RELAXATION EXERCISE TERHADAP REST HEART REAT - Trisnowiyanto, Bambang (Jurnal Phederal Penjas, 2015)
Objective: to know the immediate effect of listening to music (instrumental music hearing therapy) and muscle relaxation exercises (progressive muscle relaxation exercise) to the resting pulse rate.Background: the number of heartbeats in one minute, which gives a clear picture of the load when the activity of the heart muscle is needed at a particular time. The heart rate can be affected by physical exercise and a good atmosphere to listen to music.Subject: students of junior high school were 38 people aged 13-17 years, consisting of: 22 men and 16 women. 18 group relaxation exercises, and 20 people listen to music groups, with the inclusion: do not suffer hearing function and pain in the muscles in the body.Methods: The experimental study, two group pre test and post test design, with analysis of the influence of different test Paired-samples t test and independent-samples t test. Group 1 was given progressive relaxation exercises for 30 minutes, two groups played music instrument of Kelly Howell for 30 minutes. All treatments are given to the lying position.Results: there are significant relaxation exercises to decrease DNI p = 0.001 (p <0.05), there is no influence to listen to music on the decline DNI, p = 0.560 (p> 0.05). Providing relaxation exercises more influence on the decline compared to listening to music DNI p = 0.027 (p <0.05).conclusion: there is a significant difference between the effect of relaxation exercises with listening to the decline of the DNI. Relaxation exercises better than listening to the decline of the DNI.